Implementasi corporate social responsibility (csr) di devinsky hotel seminyak bali - Desak Made Nita Artiani; Agung Sri Sulistyawati; I Gusti Ngurah Widyatmaja (Jurnal Kepariwisataan dan Hospitalitas, 2019)
The application of social responsibility in Indonesia is regulated in law No. 40 of 2007 concerning limited company article 74 which states that social responsibility must be borne by a limited liability company. Corporate social responsibility / CSR is one of the hotel efforts to increase awareness of the surrounding community. This study aims to find out what corporate social responsibility / CSR programs are available at Devinsky Hotel Seminyak and to find out what obstacles are faced in implementing corporate social responsibility / CSR programs. This research took place at Devinsky Hotel Seminyak, using data collection techniques through observation, interviews, documentation and literature study. The analytical method used is descriptive qualitative. The data sources used are primary sources and secondary data sources. Processing and data analysis techniques through three stages, namely: data reduction, data presentation and conclusion drawing. The results of the study show that Devinsky Hotel Seminyak implements a corporate social responsibility / CSR program based on 3P, namely profit, people and the planet. These activities are providing assistance to orphanages, blood donors, beach cleaning, cooking classes, planting mangrove trees and providing village funds. Suggestions that can be given to Devinsky Hotel Seminyak is to make innovations in corporate social responsibility / CSR programs so that these activities are not monotonous. Key Words : Corporate Social Responsibility, Devinsky Hotels Seminyak